IoT-BASED SYSTEM FOR MONITORING WATER QUALITY - Kaveti Sudheer, Dr .Seelam Koteswararao, Dr.M.Paul Daniel, Daggubati Sunil (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Water-borne infections, such as dengue fever, cholera, and malaria, have emerged as serious health concerns in the modern world. Water contamination is responsible for 40% of all deaths worldwide. Drinking water quality must be monitored continuously as it is delivered to customers. This article presented a low-cost, real-time water quality measuring system design that leverages the Internet of Things (IoT). Measurements of the water's temperature, humidity, pH, and turbidity must be calculated. The poisoning of fresh water supplies is probably the green globalization's biggest fear. Constant monitoring of water quality is required to provide a safe supply of potable water. In this paper, we outline the steps taken and the features added to a framework designed to make it easy to monitor water quality in real time over the Internet of Things. Multiple sensors, built by a team with experience in water quality assessment, are integrated into the structure. The variables, such as temperature, pH, turbidity, and humidity. The central controller can configure the sensors' perceptive qualities. The ATMEGA328 can serve as the brains of the operation. In the end, WI-FI architecture allows the sensor data to be seen online. A Microcontroller is used as the automation controller for this project. When a PC sends data over Wi-Fi, the Wi-Fi module attached to the microcontroller will pick it up.The Arduino microcontroller links all of the parts together. All hardware modules receive 5v of DC voltage from a regulated power supply and are controlled by an Arduino ATMEGA328 microcontroller programmed in Embedded C using the Arduino IDE